2003
DOI: 10.14227/dt100203p6
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Testing of Orally Disintegrating Tablets

Abstract: Orally disintegrating tablets (ODT) are solid dosage forms that disintegrate in the oral cavity leaving an easy-to-swallow residue.The disintegration times are generally less than one minute.For orally disintegrating tablets,taste-masking of bitter or objectional-tasting drug substances is critical.The taste-masking aspect plays a significant role in dissolution method development,specifications,and testing.The USP 2 paddle apparatus is the most suitable and common choice for orally disintegrating tablets.Disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 5 publications
1
50
0
2
Order By: Relevance
“…The authors reported that a 2-fold increase in CF caused approximately a 5-fold increase in the tablet crushing strength to 130 N, and a 2-fold increase in DT to 78 seconds. Commercially available ODT tablets have diameters ranging from 9 mm to 17.5 mm and at the larger diameters of13 mm and greater, they can accommodate higher drug dosage of 100mg (El-Arini and Clas, 2002;Klancke, 2003;McLaughlin et al, 90 2009) (Table 1). …”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that a 2-fold increase in CF caused approximately a 5-fold increase in the tablet crushing strength to 130 N, and a 2-fold increase in DT to 78 seconds. Commercially available ODT tablets have diameters ranging from 9 mm to 17.5 mm and at the larger diameters of13 mm and greater, they can accommodate higher drug dosage of 100mg (El-Arini and Clas, 2002;Klancke, 2003;McLaughlin et al, 90 2009) (Table 1). …”
Section: Introductionmentioning
confidence: 99%
“…Typically, the dissolution of ODTs is very fast when using USP monograph conditions. Hence, lower paddle speeds might yield more discriminating dissolution profiles (Klancke, 2003;Battu et al, 2007). Therefore, in vitro dissolution studies were also conducted at a lower paddle speed of 25 rpm to select the optimized ODT formulation.…”
Section: In Vitro Dissolution Studiesmentioning
confidence: 99%
“…It is apparent that in the first 5 min, 89.0 ± 3.7 % of the drug was dissolved in the medium which increased to 94.1 ± 0.6 % in 15 min. According to the literature, the amount of drug dissolved from sublingual tablets must exceed 80 % in 15 min (20). Thus, the prepared optimized tablet met the above mentioned dissolution requirement.…”
Section: Drug Content and Dissolution Studiesmentioning
confidence: 99%